Chinese Preschool Children's Home Numeracy Experiences and their Mathematical Abilities. (March 2023) - Pan, Yuejuan; Hu, Bi Ying; Hunt, Jessica; Wu, Zhongling; Chen, Yuewen; He, Mengyang
The purpose of the present study was to examine the association between Chinese preschool children's home numeracy experiences and their mathematical abilities. The parents of 515 4- to 5-year-old preschool children reported their frequency of participation in home numeracy activities, and the children were assessed on their math ability. The results revealed that the parents engaged in both formal and informal math activities at home. Family socioeconomic status showed significant positive correlations with number game and number application activities. Parental involvement in number skills activities positively predicted young children's formal and informal math ability, while number application activities positively predicted young children's informal math ability. These results suggest that parents should pay attention to both formal and informal activities in support of their children's math learning at home.